LPPM Umri Memberikan Stimulus UMKM Melalui PKM Pada Usaha Kerupuk Maju Jaya Untuk Mendukung Upaya Mengetaskan Stunting Dari Produk Ikan Lele - Purwanto, Hadi; Sunanto, Sunanto; Hudi, Ilham; Nurhaini, Siti; Ayu Pramesti, Diah (LPPM UMRI, 2023)
Stunting is a chronic malnutrition problem caused by insufficient nutritional intake for a long time due to feeding that is not in accordance with nutritional needs. The incidence of stunting in children under five can occur due to lack or low quality of protein containing essential amino acids. Based on data obtained from the Kampar district health office, it was found that there was a stunting prevalence of 32.99% (in 2020), in 2021 and a prevalence of 23.07%, and in 2022 there was an increase in prevalence of 25.7%. To support the kampar district government program to eradicate free stanting, c In 100 grams of catfish contains protein 20.0%-46.6% (w/k), fat + 20.8 (w/k), minerals + 14.6% (w/k), water and + 6.81% (w/k). Each part of catfish has nutritional content that can be useful if consumed such as catfish head contains 50.94% protein, meat 17.7%, fish bones have a nutritional content rich in calcium which is 39.24%.Crackers are complementary foods that are favored by children because crackers are foods that have a crunchy and savory texture, This is what underlies the emergence of new innovations for stunting prevention made from catfish which is rich in protein.